Efektifitas Active Learning pada Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Ibtidaiyah Al Fithrah Surabaya - Qumruin Nurul Laila (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2016)
The Subject study of this research is active learning in the learning of Social Sciences implemented in Islamic Elementary School (MI) neighborhood of Al fithrah Surabaya. In this case, researchers wanted to find active learning which is implemented in Fourth grade of Islamic Elementary School Al fithrah Surabaya, and wanted to know the effectiveness of active learning that is implemented at Fourth grade of Islamic Elementary School Al Fithrah Surabaya. The problems of this research is how the implementation of active learning in teaching Social Sciences in MI Al fithrah Surabaya, as well as how the effectiveness of active learning in teaching Social Sciences in MI Al fithrah Surabaya. This study is an experimental research type with quantitative research approach, in which researchers apply Parametric Test Statistics for research ratio data (numeric data). While the statistical test process using a technique unpaired T test sample because there is different treatment of one of the sampling. The data collection include observation, interviews, documentary studies and tests on the sample. In the table the results of two independent samples t test, this research produced significant value of 0.00. Can be explained that 0.000 <0.01, which means that H0 was rejected while H1 was accepted. The big difference in variance data on both samples showed that the application of active learning methods affect the value of Mid Semester Tes (UTS) social studies in other words there is the effectiveness of active learning methods to improve and increase the ability of students in social studies.